Estrutura e propriedade luminescente da solução sólida de titanato de chumbo, estrôncio e cálcio - Milanez, Juliana (2008)
The lead, strontium and calcium titanate, (Pb, Sr, Ca)TiO3 (PSCT), is a solid material, which has its structure as a prototype of mineral perovskita (CaTiO3) with general formula ABX3. The solid solution of PSCT has been obtained by the polymeric precursor method and characterized by different techniques. Many of the properties observed for the titanates are directly related to the structure of the material, especially in regard to their organization. Therefore, knowing the material s degree of structural organization can help to predict its properties and possible applications. In this work it is presented a series of experimental trials that allowed us to evaluate the structural order at short, medium and long range of the material. Among those we can mentioned, DRX, FTRaman, XANES, spectroscopy in the UV-Vis region and photoluminescence emission. The study of structural order and disorder in the PSCT material, turned possible to characterize the effect of modifier lattice on the structure, linking the results to favorable conditions for the issuance of FL emission.